A Lab of One's Own : Science and Suffrage in the First Wold War - Patricia Fara (Oxford University Press, 2018)
Female scientists, doctors, and engineers experienced independence and responsibility during the First World War. Suffragists including Virginia Woolf's sister, Ray Strachey, aligned themselves with scientific and technological progress, and mobilized women to enter conventionally male domains such as engineering and medicine. Profiles include mental health pioneer Isabel Emslie, chemist and co-inventor of tear gas Martha Whiteley, Scottish army doctor Mona Geddes, and botanist Helen Gwynne Vaughan. Though suffragist Millicent Fawcett declared triumphantly that "the war revolutionized the industrial position of women. It found them serfs, and left them free," the truth was very different. Although women had helped the country to victory and won the vote for those over thirty, they had lost the battle for equality. Men returning from the Front reclaimed their jobs, and conventional hierarchies were re-established. Fara examines how these pioneers, temporarily allowed into an exclusive world before the door slammed shut again, paved the way for today's women scientists.